Influence of growth rate on homoepitaxial growth of AlN at 1450 °C by hydride vapor phase epitaxy. (1st November 2022) - Kumagai, Yoshinao; Goto, Ken; Nagashima, Toru; Yamamoto, Reo; Boćkowski, Michał; Kotani, Junji
Abstract: The influence of growth rate on the homoepitaxial growth of AlN at 1450 °C by hydride vapor phase epitaxy on bulk AlN(0001) substrates was studied. X-ray diffraction and Raman spectroscopy revealed that high structural quality comparable to that of the initial substrate can be achieved even when the growth rate is increased to over 150 μ m h −1 . Although the concentration of Si impurities increased with increasing growth rate, a freestanding AlN substrate prepared from a homoepitaxial layer grown at 155.6 μ m h −1 showed a steep optical absorption edge at 207 nm and high optical transmittance at longer wavelengths.